PENGARUH SERVANT LEADERSHIP STYLE DAN KOMUNIKASI INTERPERSONAL TERHADAP MOTIVASI KERJA PEGAWAI MELALUI KOMITMEN ORGANISASI. - Danang Khurniawan; Woro Utari; Indra Prasetyo (Journal of Applied Management and Accounting Science, 2023)
The purpose of this study, among others, is to describe work motivation, organizational commitment, Servant Leadership Style and interpersonal communication of employees at the Pusda Office of Bojonegoro Regency. To analyze the influence between Servant Leadership Style and interpersonal communication on organizational commitment. To analyze the effect of Servant Leadership Style, interpersonal communication and organizational commitment on employee work motivation. To analyze the influence between Servant Leadership Style and interpersonal communication on employee work motivation through organizational commitment. This type of research is explanatory research and the approach in this research is quantitative. The population of this study were all employees of the Pusda Office of Bojonegoro Regency, amounting to 52 people. The right technique in this research is using total sampling or saturated sampling, so the sample used is 52 people. In this study, data analysis used Structural Equation Modeling (SEM) and PLS (Partial Least Square) software. The results showed Servant Leadership Style, interpersonal communication, organizational commitment and work motivation in the high category. There is no significant effect between Servant Leadership Style on organizational commitment. There is a significant influence between interpersonal communication on organizational commitment. There is no significant effect between Servant Leadership Style on work motivation. There is a significant influence between interpersonal communication on work motivation. There is a significant influence between organizational commitment to work motivation. There is no significant effect between Servant Leadership Style on work motivation through organizational commitment. There is a significant influence between interpersonal communication on work motivation through organizational commitment